Design and Development of a Web-Based Information System for the Talent Internship Program - Wahda; Ryan Setiawan; Anisah (Jurnal Armada Informatika, 2026)
The Talent Internship Program at the Aceh Transportation Agency is currently managed manually, resulting in delays in data processing, recording errors, and difficulties in monitoring participant activities. This study aims to design and develop an integrated web-based Information System for the Talent Internship Program to improve the efficiency, effectiveness, and accuracy of internship administration management.The research employed the Prototyping method, covering requirements gathering, design, prototype development, iterative evaluation, and system implementation. The system was built using PHP, JavaScript, Bootstrap framework, and MySQL database. System testing was conducted using the Black Box Testing method.The results show that the developed system successfully integrates all administrative processes—including registration, attendance, logbook, assignments, reports, assessment, and certification—into a single web-based platform with four user roles (Intern, Mentor, Admin, and Leader). The system functions well according to user requirements and significantly accelerates administrative processes while improving real-time monitoring quality.Conclusion: The implementation of this system makes the management of the Talent Internship Program at the Aceh Transportation Agency more effective, efficient, structured, and supportive of digital transformation in government institutions.Keywords: Internship Information System, Talent Internship Program, Web-Based Application, Prototyping Method, Black Box Testing